A possible mechanism of destruction of coastal trees by tsunamis : a hydrodynamic study on effects of coastal steep hills - Huang, Zhenhua (2013)
In this paper, experimental and numerical studies are presented to understand why some trees close to the shoreline survived the 25 October 2010 Mentawai tsunami, while trees further inland before a steep coastal hill were all destroyed. A set of experiments were performed in a wave flume to measure the flow depths and forces acting on tree models, and the experimental results were used to verify our numerical model. Cross-shore distribution of the flow depth and the flow-induced bending moment acting on tree trunks were studied using our numerical model. Our results show that the presence of the steep hill increased both the flow depth and the bending moment acting on trees close to the steep hill, and might be an important mechanism responsible for the destruction of coastal trees.